Personal and General Views on Aging, Non-Communicable Diseases, and Their Interaction as Cross-Sectional Correlates of Vigorous Physical Activity in UK Individuals Aged 50 - Mezza, Fabrizio; Lemmo, Daniela; Freda, Maria Francesca; Tischler, Victoria; Stephan, Blossom C. M.; Mataró, Maria; Sabatini, Serena (Healthcare (Basel), 2025)
Background: This study investigated the cross-sectional associations of personal and general views on aging, number of non-communicable diseases, and their interactions as cross-sectional predictors of vigorous physical activity. Methods: Participants were 1699 individuals aged 50 years and over (Mean age = 67.79) and living in the community in the UK; 70.8% were women. Participants completed measures assessing Awareness of Age-Related Gains and Losses (AARC-Gains; AARC-Losses; indicators of personal views on aging), Expectations Regarding Aging (ERA; indicator of general views on aging), vigorous physical activity in the last month, non-communicable disease status, and sociodemographic questions. Linear regression models were used. Results: After having adjusted for age, sex, education, marital status, and working status, higher AARC-Gains, lower AARC-Losses, more positive ERA, and fewer non-communicable diseases were cross-sectionally associated with greater likelihood of engagement with vigorous physical activity (Adjusted models Odds Ratio (OR) of 1.08; 0.86; and 1.06, respectively). The interactions of AARC-Gains and AARC-Losses with number of non-communicable diseases as cross-sectional predictors of likelihood of engagement with vigorous physical activity were not statistically significant. The interaction between ERA (i.e., General Views on Aging) and number of non-communicable diseases was a statistically significant cross-sectional predictor of likelihood of engagement with vigorous physical activity (OR = 0.99; p = 0.044). Conclusions: Having more positive and less negative views on aging may prompt vigorous physical activity engagement. Moreover, positive general views of aging may be particularly important for physical activity among those who have one or more non-communicable diseases. Although we cannot infer causality, promoting positive views on aging and decreasing negative views on aging could help fostering active aging, especially among those with physical health conditions.